Transformative Learning in Science Education: Bibliometric Analysis - Henukh, Anderias; Setiawan, Agus; Rusdiana, Dadi; Syukri, Muhammad; Agustin, Mubiar (Asian Journal of Science Education, 2024)
This research aims to gain a broad understanding of Transformative Learning in science education (TLSC) and to find out the most popular research topics today. Vosviewer was used as a tool to image keywords and finally to describe TLSC research areas. This research was conducted through bibliometric analysis using Scopus data sources with a total of 497 documents obtained from 2014-2024. The results showed that the number of publications on TLSC has fluctuated in the last ten years. The largest decrease occurred in 20222 and the largest increase in 2023. The United States is the country with the most publications about TLSC with 183 documents. The most publications about TLSC are in the Sustainability Switzerland Journal. Keyword analysis shows that in the last ten years, research on TLSC is related to science learning, students, learning, environmental education, sustainability education, critical thinking, creativity, sustainable development, teacher education, project based learning, personnel development and professional aspects. In this regard, this recommended bibliometric analysis provides a useful understanding of the main topics covered in the discipline of TLSC in the context of Science Learning.